Identifying temperature breaches and breaks in the export cold chain of fresh hake from Namibia (Walvis Bay) to Europe (Spain) - Neethling, Chelna (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.